LEARNING MUSIC THROUGH RHYTHMIC MOVEMENTS IN MALAYSIA - Md Jais Ismail; Loo Fung Chiat; Azu Farhana Anuar (UUM Press, 2021)
Purpose - Music class should function as a class that triggers joy and a platform for students to express their feelings. Based on observation, there are music teachers who teach singing and the playing of musical instruments based traditionally on a teacher-centered approach. This has caused music classes to become passive and dull, with unexcited students that would cause them to lose focus in the class. The purpose of this research is to investigate the application of rhythmic movements, using one of the components from Dalcrozeâ€™s Eurhythmics as an activity to develop active and fun music classes, hence to improve studentsâ€™ music performance skills. Methodology - The study was carried out within the framework of a ten-week action-research design involving 35 primary school students at Putrajaya, Malaysia. Data collection was through group observation on studentsâ€™ musical behaviours. Researchers also conducted an in-depth interview with rhythmic movement experts. Findings - Result shows that there is a significant change of musical behaviours among primary students from week 8 to week 10. Experts agree that rhythmic movement can create a meaningful music class with the active participation of students. Three rhythmic procedures have been recommended by the experts to strengthen a music class pedagogy.    Significance - Learning music through movements has turned music classes into active and fun places. Rhythmic movement activity has made music lessons to become more meaningful. This study has helped students to explore music through movements, creating an environment in which they have the chance to play, communicate with each other, learn through observation and express their creativity in their own way. This intervention helps students to grasp almost all the music concepts while doing activities. This study has also provided ideas for teachers to integrate rhythmic movements into the music instructional process.